LEARNING WITH CORPORA IN ENGLISH LANGUAGE TEACHING: PEDAGOGICAL IMPLICATIONS - Isomiddinova Diyora, (Ta'limda raqamli texnologiyalarni tadbiq etishning zamonaviy tendensiyalari va rivojlanish omillari, 2026)
Annotation: This paper explores the pedagogical implications of using corpora in English language teaching. Grounded in applied linguistics and corpus-based research, the study examines how corpora support second language acquisition, particularly in developing writing, vocabulary, and grammatical competence. Drawing on recent studies, the paper highlights both the advantages and challenges of corpus use in educational contexts. It argues that while corpora enhance learner autonomy, critical thinking, and engagement, issues such as accessibility, time constraints, and technical limitations remain. The paper also proposes recommendations for improving corpus-based instruction, including integrating modern technologies and promoting user-friendly corpus tools. Overall, the study suggests that corpus-based learning has significant potential to improve English language education when implemented effectively.